Quantitative Data Analysis of Water Concept in English Water Management Metadiscourse - Kovalyk, Nataliia; Tymochko, Lesia (Respectus Philologicus, 2020)
This paper deals with the comparative analysis of the possibility to apply both linguo-cognitive and quantitative methods in the study of structure of mental units, e.g. concepts. The current research continues our overall and integrated study of English ecological discourse and is the next in a number of logical research series of this scientific challenge (Ковалик 2017; Ковалик, Тимочко 2018). The study object of this paper is WATER concept in English water management metadiscourse. The research is carried out on the basis of the original text of the EU Water Framework Directive 2000/60 / EC. The aim of the paper is not only to conduct a frame-based analysis of WATER concept using Svitlana Zhabotynska’s methodology of conceptual analysis (Жаботинська 1999) but also to analyse the concept occurrences in the researchable metadiscourse. In the present investigation, the conceptual structure of WATER concept is modelled through basic frame schemas and is considered as an open system. The research takes a new look at the application of linguo-cognitive and quantitative data analyses in the study of WATER concept in English water management metadiscourse.